2013
DOI: 10.1111/are.12339
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination strategies with oral booster for surubim hybrid (Pseudoplatystoma corruscans × P. reticulatum) against haemorrhagic septicaemia

Abstract: This study evaluated the efficiency of differently prepared vaccines against Aeromonas hydrophila in the hybrid surubim (Pseudoplatystoma corruscans 9 P. reticulatum). Survival and haematoimmunological parameters were compared between the treatments: non-vaccinated fish (C); bacterin-vaccinated fish (B); bacterin plus oral booster vaccinated fish (B+O); bacterin and toxoid-vaccinated fish (B+T) and bacterin, toxoid and oral booster-vaccinated fish (B+T+O). Fourteendays vaccinated fish from B+O and B+T+O were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Thus, 100mL of vaccine was sprayed using a sterile plastic spray bottle for each kilogram of commercial diet or the diet containing probiotic following methodology previously described by (PEREIRA et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 100mL of vaccine was sprayed using a sterile plastic spray bottle for each kilogram of commercial diet or the diet containing probiotic following methodology previously described by (PEREIRA et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The diet containing vaccine was also provided four times a day (3% of the biomass). The vaccination protocol and sampling was carried out according PEREIRA et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Sirimanapong [49] showed that the number of lymphocyte was also signi cantly higher in the vaccinated sh by 1, 14 and 21 days post-immunization. In contrast, Pereira [19] reported that the lymphocytes counts were not statistically different after oral vaccination in surubim hybrid (Pseudoplatystoma corruscans x P. reticulatum). However, the neutrophils and monocytes in the current study played a signi cant role in the early immune response followed by the lymphocytes.…”
Section: Discussionmentioning
confidence: 88%
“…To address the losses due to Streptococcosis and MAS, antibiotics are the only option for farmers and the use of antibiotics results in development of antibiotic resistance strains, bio-accumulation, changes the physio-chemical properties of water, imbalance of bacterial microbiota in sh body or in the habitat [17,18]. To solve these di culties, application of sh vaccines is an alternative to minimize the different infectious bacterial diseases [19].…”
Section: Introductionmentioning
confidence: 99%
“…To address the losses due to Streptococcosis and MAS, antibiotics are the only option for farmers and the use of antibiotics results in development of antibiotic resistance strains, bio-accumulation, changes the physio-chemical properties of water, imbalance of bacterial microbiota in fish body or in the habitat [22][23][24]. To solve these difficulties, application of fish vaccines is an alternative to minimize the different infectious bacterial diseases [25,26].…”
Section: Introductionmentioning
confidence: 99%